BORDER DIPLOMACY PEMERINTAH REPUBLIK INDONESIA DALAM MENANGANI PENYELUNDUPAN GULA DI ENTIKONG - Haliffa Haqqi, Prisma Kristi, Christy Damayanti & (Transformasi, 2018)
This research described and analyzed the problem concerning border diplomacy conducted by Indonesian government in dealing with sugar smuggling case in Entikong-Tebedu border, Malaysia. Sugar smuggling in Entikong border, West Borneo often occurs through either legal or illegal stripe. This sugar smuggling occurs due to economic condition, sugar production not fulfilling the people’s need in Entikong border. Jokowi constructed Entikong Integrated State Cross Border Post (Pos Lintas Batas Negara Terpadu Entikong) to facilitate the cross-border activity better. However, sugar smuggling case remains to occur because of many rat runs along Entikong border line that cannot be afforded by the border security guards. The author employed border diplomacy, border security, and bilateral relation theories. The objective of research was to find out what Indonesian Government’s border diplomacy is in dealing with sugar smuggling case in Entikong border. The research method employed in this study was qualitative one with primary and secondary data. Data collection was carried out using interview and documentation methods, and the data collected was analyzed descriptively. From the result of research on border diplomacy in dealing with sugar smuggling case in Entikong, it could be found that the enactment of border diplomacy constituting bilateral diplomacy by Indonesian and Malaysian Governments, and border security guards such as Indonesian Army and Police (TNI-Pori), and Customs provided Border Trade Agreement (BTA) review, the cooperation concerning the management of Entikong-Tebedu border security and cross border activities to prevent sugar smuggling from occurring.Keywords: Border Diplomacy, Border Security, Sugar Smuggling, Entikong Border